2022
DOI: 10.1515/astro-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

New triple-mode high-amplitude Delta Scuti variables

Abstract: I present a detection of four new triple-mode high-amplitude Delta Scuti variables, pulsating in the fundamental, first, and second overtone modes. This is a new addition to the ten known cases in the Galaxy. I used the data of ASAS-SN and analyzed them using the WinEfk code by V. P. Goranskij. Light elements and parameters of the light curves were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The smaller Galactic Scuti amplitudes, caused by smaller temperature fluctuations lead to a flatter PC relation at maximum light. Hence, we have good support for the HIF stellar photosphere theory as described in Simon et al 1993;Das et al 2020, and references therein. We also note that there is some controversy over the pulsation mode of Scuti stars and in fact whether they may be pulsating in a number of modes and/or have a non-radial component (Netzel et al 2022;Lv et al 2022;Khruslov 2022;Netzel & Smolec 2022). When we cross-checked our sample with the triple mode stars as listed in Netzel et al (2022), we found 32 such stars in our sample.…”
Section: A Possible Theoretical Explanationmentioning
confidence: 90%
“…The smaller Galactic Scuti amplitudes, caused by smaller temperature fluctuations lead to a flatter PC relation at maximum light. Hence, we have good support for the HIF stellar photosphere theory as described in Simon et al 1993;Das et al 2020, and references therein. We also note that there is some controversy over the pulsation mode of Scuti stars and in fact whether they may be pulsating in a number of modes and/or have a non-radial component (Netzel et al 2022;Lv et al 2022;Khruslov 2022;Netzel & Smolec 2022). When we cross-checked our sample with the triple mode stars as listed in Netzel et al (2022), we found 32 such stars in our sample.…”
Section: A Possible Theoretical Explanationmentioning
confidence: 90%
“…High-amplitude δ Scuti stars (hereafter HADS) are a subclass of δ Scuti stars, who always have larger amplitudes and slower rotations. Most of the HADS show single or double radial pulsation modes (Niu et al 2013(Niu et al , 2017Xue et al 2018;Alton 2019;Bowman et al 2021;Daszyńska-Daszkiewicz et al 2022;Alton 2022a,b,c), and some of them have three radial pulsation modes (Handler et al 1998;Wils et al 2008;Mow et al 2016;Yang et al 2021;Kazarovets et al 2020;Khruslov 2014Khruslov , 2022Poleski et al 2010; or even some non-radial pulsation modes (Poretti et al 2011). SX Phoenicis (SX Phe) stars, a subgroup of HADS, are old Population II stars, which are characterized by high amplitudes of pulsation, low metallicity, and large spatial motion.…”
Section: Introductionmentioning
confidence: 99%
“…High-amplitude δ-Scuti stars (hereafter HADS) are a subclass of δ-Scuti stars, which always have larger amplitudes and slower rotations. Most of the HADS show single or double radial-pulsation modes (Niu et al 2013(Niu et al , 2017Xue et al 2018;Alton 2019, Bowman et al 2021Alton 2022aAlton , 2022bDaszyńska-Daszkiewicz et al 2022), and some of them have three radial-pulsation modes (Handler et al 1998;Wils et al 2008;Mow et al 2016;Yang et al 2021, Poleski et al 2010Khruslov 2014;Kazarovets et al 2020;Khruslov 2022;, or even some nonradial pulsation modes (Poretti et al 2011) , V = 11.86 mag) is an Population II SX Phe star pulsating with a single radial mode (Ceraski 1904;Nijland 1923;McNamara & Feltz 1980;Szeidl & Mahdy 1981;Joner 1982;Hintz & Joner 1997;Kiss & Derekas 2000;Zhou et al 2002;Blake et al 2003), which shows a continuous linearperiod variation rate of (1/P 0 )( dP 0 / dt) = 1.19(13) × 10 −8 yr −1 (Yang et al 2012). Although XX Cyg has a clean periodogram (which consists of the fundamental frequency f 0 = 7.4148 c day −1 and its harmonics), the residuals in the O − C diagram have deviations of about 0.001-0.005 day, which is an order of magnitude larger than the uncertainties of the times of maximum light (TML; about 0.0001 day).…”
Section: Introductionmentioning
confidence: 99%